Pengaruh Aktivitas Menghafal Al-Qur’an Terhadap Prestasi Belajar Siswa - Nuril Qodri Mubarok; Ilhamus Subhaniyah; Siti Aisyatul Arifah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Education is a guideline for a nation in improving the quality of society. As for the benchmark of a developed nation, one of them can be seen from the success of its education. The main activity in education is learning. Either learn the lessons of madrasa or cottage, either general science or science of the Qur'an. In a learning certainly not escape the name of memorization. Either memorizing general knowledge or knowledge of the Qur'an. This research is purposeful. First, to find out how the student's strategy is done in sorting out the time between learning at school by memorizing the Qur'an. Second, to determine the constraints felt by students during the learning process. Third, to find out what changes are experienced by students in general education, besides he became a memorizer of the Qur'an. The method used in this study uses a qualitative approach, with the type of multi-Case Study of the use of the number of cases more than one in general to obtain more detailed data. This study was obtained through interviews with students concerned in two different places. The results of this study in two different places show that memorizing the Qur'an also affects students ' learning performance. With several achievement strategies carried out, such as liking existing lessons, doing assignments, and asking for the blessing of parents is something that can support learning achievement. Although there will be some obstacles that will be encountered when in the process of memorizing or achieving learning achievements, but there will definitely be a solution to every problem that will be encountered. So with the right solution for every problem or obstacle when the process of achieving Achievements with the Qur'an, there will be changes that occur before and after memorizing the Qur'an.